Regulation of IFN-γ-mediated PD-L1 expression by MYC in colorectal cancer with wild-type KRAS and TP53 and its clinical implications - Guo, Libin; Tang, Xiaoqiong; Wong, Sin Wa; Guo, Anyuan; Lin, Yao; Kwok, Hang Fai (Frontiers in Pharmacology, 2022)
In the tumor microenvironment, interferon gamma (IFN-γ) secreted by tumor-infiltrating lymphocytes can upregulate programmed cell death 1 ligand 1 (PD-L1) expression in many cancers. The present study evaluated the expression of PD-L1 in selected colorectal cancer cell lines with IFN-γ treatment and explored the correlation between PD-L1 expression and KRAS/TP53 mutation status. The selected colorectal cancer cell lines had known KRAS mutations or TP53 mutations. In vitro experiments were used to explore the mechanism underlying KRAS- and TP53-related anti-PD-1/PD-L1 immunotherapy. Firstly, TCGA data analysis for gene expression and overall survival and an in vitro study revealed that the wild-type KRAS/TP53 cell lines exhibited hyperresponsiveness to IFN-γ exposure and correlated with better survival in patients receiving anti-PD-1/PD-L1 treatment. Secondly, experimental data revealed that IFN-γ induced the upregulation of PD-L1 mainly through regulating MYC in wild-type KRAS and TP53 colorectal cancers. Our results indicate that the wild-type KRAS/TP53 colorectal cancer cell lines may respond better to IFN-γ treatment, which causes increased PD-L1 expression and may be a mechanism underlying the better responses to anti-PD-1/PD-L1 therapies in wild-type KRAS and wild-type TP53 colorectal cancer. Our findings revealed that the response to anti-PD-1/PD-L1 cancer immunotherapy frequently happened in wild-type KRAS and TP53 colorectal cancers, which were also found to show higher PD-L1 expression. Furthermore, the experimental results suggest that IFN-γ regulated PD-L1 expression through the regulation of MYC, which may further affect the response to PD-1/PD-L1 cancer immunotherapy. These results suggest a novel potential treatment strategy for enhancing the efficacy of PD-1/PD-L1 blockade immunotherapy in most colorectal cancer patients.